Parasit Gastrointestinal pada Sapi di Daerah Aliran Sungai Progo Yogyakarta - Yudhi Ratna Nugraheni; Dwi Priyowidodo; Joko Prastowo; Eryl Sri Rohayati; Ana Sahara; Aan Awaludin (Politeknik Negeri Jember, 2018)
The aim of study was investigate gastrointestinal disease on cow fed forage from Progo watershed. Sixty three feses samples were taken from cows on Progo watershed. The method of feses analysis used was sentrifuge and Parfitt Bank. The results showed that 63 samples of cows feces were examined, among 25 were infected by Fasciola sp., 7 Paramphistomum sp., 14 Strongyle, and 9 Coccidiosis. The conclusion was the prevalence of gastrointestinal disease in cows was dominant incidence of Fasciolosis by 40%, Strongyle 22%, 14% Coccidiosis, and Paramphistomum sp.11%.